Study on Designing and Manufacturing the DS-12 Freeze - Drying System Using Infrared Radiation Heating Process - Giurgiulescu, Liviu; , Phong Le Thanh; Linh T.K. Do,; Tan Dzung Nguyen, (Journal of Technical Education Science, 2024)
Freeze drying is a process of separating water inside material (food) by changing its state directly from the solid state (ice) after freezing to vapor state in a low temperature and low-pressure environment, below the triple point O (0.0098oC, 4.58mmHg). Because the drying process is conducted in an absolute vacuum and heat transfer during the drying process is mainly radiation and conduction, while convection is not possible, so the drying time is prolonged, and energy is inefficient. Therefore, this study will calculate, design, and manufacture the DS-12 freeze drying system that provides heat for the freeze-drying process by using infrared radiation. When applying the optimal technological mode for freeze-drying: drying chamber’s temperature is 20.58oC; drying chamber’s pressure is 0.411 mmHg; drying time is 14.785 hours, results showed that energy costs per 1 kg of product reduced to a minimum of 4.75 kWh, saving nearly 25% of total energy costs as compared to the freeze-drying process using heat from conventional thermistors. The final product has very good quality, the loss of 10-HDA (freshness) after drying is only 0.65% and moisture of product is 4.22% (less than 4.5%) which meets the technological requirements. The results of this research can be fully applied to large scale production.